Intensitas Komunikasi Antara Anak Dengan Orang Tua Dan Self Regulation pada Remaja Pesantren - Asizah, * (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. This research is to find out if anything there is a relationship between the intensity of parent-child communication with adolescent self-regulation in schools. The population used in this study is a teenage boarding school educated men who are MTS / Junior High School, class VIII, as many as 84 people. Sampling using purposive sampling. Methods of data collection using the Likert method to scale communication and self-regulation. The results of data analysis showed no association between communication with the self-regulation of rhitung = 0.510 with rtabel = 0.220, where rhitung (0.510)> rtabel (.220). The hypothesis stating no connection between the intensity of parent-child communication with adolescent self-regulation on schools received a correlation coeffi-cient of 51%).Â Keywords: Intensity of Communication, Self Regulation